De l'immersion à la glossodiversité (en domaine de politique linguistique scolaire) - Pierre Escudé (Lengas)
We will look at the notions of immersion and glossodiversity through the lens of French language policy. The latter is guided by a founding monolingual ideology, opposed to any deviance: varieties within the same language, a fortiori diversity of languages, bilingualism, plurilingualism. In fact, when it comes to managing populations within the territory of a nation-state, this representation turns bilingualism into an oppositional myth, rather than a balanced social reality. A return to linguistics and a grounding in didactics - making it possible to manage the learning of this reality of language in educational systems and social life - would make it possible to extricate ourselves from the infertile opposition between the two ideologies of monolingualism and bilingualism. How can we manage variety within unity? Through a language policy guided by what we learn from linguistics and didactics, and no longer from a Westphalian vision of an abstractly monolingual state.